Pressed by a Double Loyalty : Hungarian Attendance at the Second Vatican Council, 1959-1965 - Fejerdy, András, 1977- (Book collections on Project MUSE., 2016)
"The Second Vatican Council is the single most influential event in the 20th century history of the Catholic Church. The book analyzes the relationship between the Council and the "Ostpolitik" of the Vatican through the history of the Hungarian presence at Vatican II. Pope John XXIII, elected in 1958, was a catalyst. The pope thought that his most urgent task was to renew contacts with the Church behind the iron curtain. Hungarian participation at the Council was also made possible by the new, pragmatic model in Hungarian church politics. After the crushing of the 1956 Revolution, churches in Hungary thought that the regime would last and were willing to compromise. Vatican II -- in the perspective of Hungary -- was not primarily an ecclesial event, but it remained closely joined to the negotiations between the Holy See and the Kádár regime: during the Council Hungary became the experimental laboratory of the Vatican's new eastern policy. Was it a Vatican decision or a Soviet instruction? Fejerdy suggests that it was a decision of the Holy See."--JSTOR website (viewed April 13, 2017).